INTERDISCIPLINARY COMPARISON OF POST GRADUATE STUDENTS FOR ACADEMIC WRITING PROFICIENCY IN ENGLISH - Khaliq, Sarwar; Khanam, Afifa (International Journal of Psychosocial Rehabilitation, 2020)
The importance of writing skill multiplies as soon as the learners become part of learning communities at higher education level. It is mainly because, the competence level of ESL (English as a second language) students is gauged through their academic writing skill. Their task to prove their worth becomes harder as it demands full command in writing research papers, argumentative essays, term papers, and analysis reports etc.The writing modules are ideally designed and implemented but as far as their outcomes are concerned, they are found mostly unfulfilled. In order to dig out the reasons, many studies are conducted and have reached to the conclusion that the nature of discipline impacts on academic writing style in addition to other multiple reasons. Therefore, a causal comparative study with 3x5factorial design was employed to investigate the impact of disciplinary factors on the academic writing proficiency in English of postgraduate(PG) learners in a Public Sector university. Taking the population of total 49 disciplines at the university, three of them were selected purposively; Education, Science and Engineering as representatives of major faculties. A test comprised of five major writing skills; Syntacticstructure, Lexical features, Paraphrasing, Coherence and Precision, was designed and conducted parallelly on the post graduate students of the three disciplines. The comparison was drawn by applying ANOVA for main effects and interactions of independent variable (discipline) and dependent variable (academic writing skills) were calculated. It was found that significant discrepancies were present in the Academic writing proficiency of the post graduate students due to the diverse nature and needs of their disciplines. The study holds substantial implications for teaching academic writing skills exclusively in diverse disciplines.